Diagnostic accuracy of two commercially available rapid assays for detection of IgG and IgM antibodies to SARS-CoV-2 compared to ELISA in a low-prevalence population - Hackner, Klaus; Errhalt, Peter; Willheim, Martin; Schragel, Felix; Grasl, Maria-Anna; Lagumdzija, Jasmina; Riegler, Waltraud; Ecker, Michael; Wechdorn, Matthias; Thalhammer, Florian; Assadian, Ojan (German Medical Science GMS Publishing House, 2020)
Background: New commercially available point-of-care (POC) immunodiagnostic tests are appearing, which may yield rapid results for anti-SARS-CoV-2 antibodies. The aim of this study was to evaluate the diagnostic accuracy of rapid antibody detection tests compared to a validated laboratory-based enzyme-linked immunosorbent assay (ELISA) and to investigate infections amongst healthcare workers (HCWs) after unprotected close contact to COVID-19 patients. Methods: Blood serum and whole blood of 130 participants were tested with NADAL COVID-19 IgG/IgM rapid test and mö-screen 2019-NCOV coronavirus test against a validated ELISA test. Infection status was evaluated using real-time polymerase-chain-reaction.Results: Acute COVID-19 infection was detected in 2.4% of exposed HCWs. Antibody tests showed an overall frequency of IgG and IgM in 5.3%, with 1.6% asymptomatic infections. The NADAL test showed a sensitivity (IgM/IgG) of 100% (100%/100%), a specificity (IgM/IgG) of 98.8% (97.6%/100 %), a PPV of 76.9% (57.1%/100%), an NPV of 100% (100%/100%), and a diagnostic accuracy of 98.8% (97.7%/100%). The mö-screen test had a sensitivity (IgM/IgG) of 90.9% (80%/100%), a specificity (IgM/IgG) of 98.8% (97.6%/100%), a PPV of 76.9% (57.1%/100%), an NPV of 99.6% (99.2%/100%), and a diagnostic accuracy of 98.5% (96.9%/100%). Conclusions: The frequency of COVID-19 infections in HCWs after unprotected close contact is higher than in the general population of a low-prevalence country. Both POC tests were useful for detecting IgG, but did not perform well for IgM, mainly due to false positive results.